Instrumentalne wykorzystywanie sondaży w dyskursach medialnych i politycznych - Guzik, Aldona; Marzęcki, Radosław (Polityka i Społeczeństwo, 2021)
Today the mass media plays a more and more important role as a source of infor-mation about different aspects of social life. Thus, it has become the main source of political knowledge as well. The more information citizens obtain from mass media, the bigger power the media has over its audience. Therefore, various players – journalists, publicists and politicians (using this feature of contemporary media) want to influence the state of social consciousness. One of the methods of such influence is the instrumen-tal use of survey results in political and media discourses. In their article the authors describe different examples of these argumentations.